Radiation and hot electron temperature measurements of short-pulse laser driven hohlraums - Brown, C; James, S; Beg, F; Constantin, C; Daskalova, R; Edwards, R; Freeman, R; Higginson, D; Morton, J; Niemann, C; Riley, D; Thomas, B; et al. (2009)
We have performed measurements of the radiation and the hot electron temperature in sub-millimetre size hohlraums driven by a high intensity short-pulse laser. The results indicate that radiation temperatures ∼80 eV can be obtained with ∼20 J of laser energy delivered on target. Radiation-hydrodynamics simulations indicate an absorption into thermal X-rays of ≲1-2%, with peak temperatures similar to those measured experimentally. Crown Copyright © 2009.